Middle to Late Eocene Changes of the Ocean Carbonate Cycle. Issue 12 (24th November 2021) - Borrelli, C.; Katz, M. E.; Toggweiler, J. R.
Abstract: Sedimentary records show that calcium carbonate (CaCO3 ) preservation fluctuated during the Eocene. These fluctuations are well documented for the equatorial Pacific. However, data from other basins are sparse. In this study, we report new middle and late Eocene bulk calcium carbonate percentages and accumulation rates from the northwestern Pacific (Ocean Drilling Program—ODP—Site 884) and the Atlantic (ODP Sites 1053, 1090, and 1263) Oceans; in addition, we calculate CaCO3 accumulation rates for sites with published percentage bulk CaCO3 to expand geographic and paleobathymetric coverage. Using these data, we investigate the response of the carbonate cycle to environmental changes (e.g., temperatures, primary productivity, weathering, and ocean circulation) at the beginning of the greenhouse‐icehouse transition (∼43–34 Ma). Our results show that in the middle to late Eocene CaCO3 accumulation rates were highly variable at different paleodepths and ocean basins suggesting that the evolution of carbonate accumulation rates over the Eocene was influenced by different processes in different locations. In particular, our data emphasize the role of surface CaCO3 production and ocean ventilation in driving changes in CaCO3 preservation and burial at the seafloor. Our study also highlights the need for a better understanding of the processes regulating CaCO3 surface production today in order to correctly interpret geological records. Plain Language Summary: Over geological timescales, CaCO3 production in the ocean surface and burial in marine sediments are important components of the global carbon cycle. A rapid increase in CaCO3 preservation at deeper depths occurred at the Eocene/Oligocene boundary. However, what drove this change is still debated. Here, we investigate CaCO3 accumulation at sites from different paleodepths and ocean basins during the middle and late Eocene (∼43–34 Ma). This is a particularly important period of time as it marks the beginning of the greenhouse‐to‐icehouse climate transition. Our results show that CaCO3 accumulation and dissolution were spatially and temporally heterogeneous. Based on this, we propose that CaCO3 production at the ocean surface, as well as changes in ocean circulation, had a fundamental role in driving CaCO3 preservation in different ocean basins. Key Points: Calculation and comparison of carbonate accumulation rates depend on solid age models Geographic and paleobathymetric carbonate accumulation rates were highly variable during the middle and late Eocene Surface carbonate production and ocean ventilation were important drivers of the middle and late Eocene carbonate accumulation rates